Sex Estimation via Morphometric Analysis of Three-Dimensional Digitally Configured Craniofacial Computed Tomography Images in a Sample of the Egyptian Population: Sex Estimation via Analysis of Craniofacial Computed Tomography Images - Muhammad, Mai; Zayed, Abeer; Hussein, Mohammed; Gamal El-Din, Dina; Mahrous, Mai (International Journal of Medical Toxicology and Forensic Medicine, 2025)
Background: Identification and verification of identity are mandatory in a variety of civil and criminal contexts. Sex estimation from morphometric craniofacial measurements in a sample of the Egyptian population. Methods: This study employed a cross-sectional design, involving 303 computed tomography images (165 males and 138 females). Twenty craniofacial measurements were studied in relation to the corresponding sex. Results: Most of the measurements were greater in males than in females. Bimastoid breadth, length of the cranial base, anteroposterior diameter of the right and left frontal sinuses, bizygomatic breadth, right maxillary sinus height, left maxillary sinus length, right and left maxillary sinus volume, and right mandibular ramus length showed a highly statistically significant difference between sex groups (P value < 0.001). Discriminant scoring was calculated to estimate sex from craniofacial measurements, and 80.6% of males and 78.9% of females in the original grouped cases were correctly classified. Conclusion: Craniofacial measurements can be used as a reliable method for sex estimation. The establishment of a comprehensive national database for craniofacial measurements is recommended for documentation purposes.